TNF receptor–activated factor 2 mediates cardiac protection through noncanonical NF-κB signaling - Evans, Sarah (JCI Insight, 2018)
To elucidate the mechanisms responsible for cytoprotective effects of TNF receptor–activated factor 2 (TRAF2) in the heart, we employed genetic gain- and loss-of-function studies ex vivo and in vivo in mice with cardiac-restricted overexpression of TRAF2 (Myh6-TRAF2(LC)). Crossing Myh6-TRAF2(LC) mice with mice lacking canonical signaling (Myh6-TRAF2(LC)/Myh6-IκBαΔN) abrogated the cytoprotective effects of TRAF2 ex vivo. In contrast, inhibiting the JAK/STAT pathway did not abrogate the cytoprotective effects of TRAF2. Transcriptional profiling of WT, Myh6-TRAF2(LC), and Myh6-TRAF2(LC)/Myh6-IκBαΔN mouse hearts suggested that the noncanonical NF-κB signaling pathway was upregulated in the Myh6-TRAF2(LC) mouse hearts. Western blotting and ELISA for the NF-κB family proteins p50, p65, p52, and RelB on nuclear and cytoplasmic extracts from naive 12-week-old WT, Myh6-TRAF2(LC), and Myh6-TRAF2(LC)/Myh6-IκBαΔN mouse hearts showed increased expression levels and increased DNA binding of p52 and RelB, whereas there was no increase in expression or DNA binding of the p50 and p65 subunits. Crossing Myh6-TRAF2(LC) mice with RelB(–/+) mice (Myh6-TRAF2(LC)/RelB(–/+)) attenuated the cytoprotective effects of TRAF2 ex vivo and in vivo. Viewed together, these results suggest that crosstalk between the canonical and noncanonical NF-κB signaling pathways is required for mediating the cytoprotective effects of TRAF2.